2009
DOI: 10.1177/0021998308099224
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of CFRP and Hybrid FRP Composites at Elevated Temperatures

Abstract: The performance of fiber reinforced polymer (FRP) composites at high temperatures is a serious concern that needs investigation before the incorporation of these composites into important engineering structures. This article presents an experimental study on the tensile properties of carbon fiber reinforced polymer (CFRP) sheets, hybrid carbon/glass fiber reinforced polymer (C/GFRP) sheets and hybrid carbon/basalt fiber reinforced polymer (C/BFRP) sheets at different temperatures. The specimens of FRP sheets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…Many experimental studies reported that external wrapping by FRP composite could remarkably increase the load-carrying ability of circular, square, and rectangular concrete columns [5][6][7]. Different types of FRPs have been used for the lateral confinement of concrete columns, which includes carbon [8][9][10][11][12][13][14], glass [7,[15][16][17][18], aramid [6,[19][20][21], polyethylene napthalate (PEN) [22,23], polyethylene terephthalate (PET) [22][23][24][25][26], and basalt [27][28][29]. These FRP composites are effectively used in enhancing the load-bearing capacity and energy absorption of masonry and reinforced concrete infrastructures.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies reported that external wrapping by FRP composite could remarkably increase the load-carrying ability of circular, square, and rectangular concrete columns [5][6][7]. Different types of FRPs have been used for the lateral confinement of concrete columns, which includes carbon [8][9][10][11][12][13][14], glass [7,[15][16][17][18], aramid [6,[19][20][21], polyethylene napthalate (PEN) [22,23], polyethylene terephthalate (PET) [22][23][24][25][26], and basalt [27][28][29]. These FRP composites are effectively used in enhancing the load-bearing capacity and energy absorption of masonry and reinforced concrete infrastructures.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of additional relevant studies performed on tensile properties of FRPs specifically used for civil engineering strengthening applications have been presented, including the work of Cao et al [12], Wang et al [13], Chowdhury et al [14], and Yu and Kodur [15]. Two basic types of test procedures (similar to those typically used at ambient temperature 1 ) were used in these prior studies: specimens were (i) heated up to a predefined temperature and then loaded up to failure (steady state (S) conditions); or (ii) loaded to a fraction of their ambient temperature strength and then heated up to failure (transient state (T) conditions).…”
Section: Frpmentioning
confidence: 99%
“…Cao et al [12] performed a series of tensile tests on CFRP and hybrid (carbon/glass fibre) FRP sheets from ambient temperature up to 200 C under steady state (S) conditions. Fig.…”
Section: Frpmentioning
confidence: 99%
“…The mechanical behaviour of CFRP is known to be strain rate dependent [2][3][4][5], especially with shear loading [4,6,7] and temperature dependent [2,3,8]. One important conclusion of these studies is that their mechanical shear behaviour can be decomposed into two different phasis: a first linear, a second non linear, followed by the final rupture of the material [4,6,9,10].…”
Section: Introductionmentioning
confidence: 99%